Diversity of arbuscular mycorrhizal fungi in soil from the Pampa Ondulada, Argentina, assesed by pyrosequencing and traditional techniques - Colombo, Roxana (2014)
The aim of this study was to assess the effects of agronomic practices on arbuscular mycorrhizal (AM) fungal community in soils from the Pampa Ondulada region (Argentina), and to compare conclusions reached when using pyrosequencing or morphological approach. AM fungal diversity was assessed in three agricultural exploitations located at the Pampa Ondulada region (Argentina) by 454 amplicon pyrosequencing and morphological (based on spore traits) approaches. Two kinds of soil managements are found in these sites (agronomic and non-agronomic). 188 Molecular Operational Taxonomic Units (MOTUs) and 29 morphological species of AM fungi were identified in total. Non effect of soil management on AM richness was detected. AM fungal communities were more diverse and equitable in absence of agronomic management. In contrast, results on beta diversity varied according to the methodology used. We concluded that agronomic management of soil has a negative effect on AM fungal community biodiversity in the Pampa Ondulada region. We also conclude that both methodologies complement each other in the study of AM fungal ecology. This study greatly improved the knowledge about AM fungi in South America where the molecular diversity of AM fungi was practically unknown.